A CURIOUS CASE OF PITUITARY STALK THICKENING – LYMPHOCYTIC INFUNDIBULONEUROHYPOPHYSITIS - Yang, Lian Zi; Velaiutham, Shanty A/P (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Hypophysitis is a rare inflammatory disorder that affects the pituitary gland and infundibulum. Lymphocytic infundibuloneurohypophysitis (LINH), one of the causes of primary hypophysitis, is a rare autoimmune inflammatory process that selectively affects the neurohypophysis and infundibulum, typically presenting with arginine vasopressin deficiency (AVP-D). Magnetic resonance imaging (MRI) with contrast demonstrates thickening of the pituitary stalk, enlargement of the neurohypophysis, or both with homogeneous enhancement. The inflammatory process in LINH can be self-limited and regression can be seen radiologically during follow-up. CASE A 22-year-old male presented with sudden onset polyuria and polydipsia in 2016, with clinical and laboratory findings consistent with AVP-D. Brain MRI demonstrated enlargement of the pituitary stalk, measuring 6 mm, and absence of the posterior pituitary bright spot. Other anterior pituitary hormones were normal, except for mildly raised prolactin levels. Investigations for secondary aetiologies were not significant. He was given a trial of glucocorticoid treatment. Serial brain MRI showed a reduction of the pituitary stalk, but AVP-D persisted, and he was diagnosed with LINH. The evaluation of a patient with thickening of the pituitary stalk involves assessing the function of both the anterior and posterior pituitary glands and identifying the underlying cause. LINH is characterized by lymphocytic infiltration, leading to the eventual destruction of the pituitary tissue accompanied by varying degrees of pituitary dysfunction. Histopathology remains the gold standard for diagnosis, and definite diagnosis can only be established via pituitary stalk biopsy. Due to the wide range of possible aetiologies, caution and close monitoring are strongly recommended for the treatment of presumed cases lacking histopathologic confirmation. CONCLUSION There are no evidence-based guidelines on the management of LINH due to its rarity. The glucocorticoid response rate has been variable. An individual approach is warranted. A conservative medical approach is often used as LINH is often self-limiting, especially when symptoms of mass effect are absent.